Bio‐Metabolism‐Driven Crystalline‐Engineering of CdS Quantum Dots for Highly Active Photocatalytic H 2 Evolution - Xu, Li‐Xia; Wang, Yan‐Zhai; Zhou, Dao; Chen, Meng‐Yuan; Yang, Xue‐Jin; Ye, Xiao‐Mei; Yong, Yang‐Chun (ChemistrySelect (Weinheim), 2021)
Biosynthesis was considered as a green and sustainable approach for nanomaterials fabrication. However, it is still quite challenging to fine tune the biosynthesis process for high‐quality photocatalytic nanomaterials. In this study, an aerobic approach for biosynthesis of photocatalytic CdS quantum dots (QDs) by Shewanella oneidensis MR‐1 was developed. Interestingly, it was found that by simply tuning the concentration of substrates, the crystalline structure of the CdS QDs was transformed between cubic phase and hexagonal phase. The hexagonal CdS QDs synthesized by simple substrate‐metabolism regulation exhibited high photocatalytic H 2 evolution activity (21 mmol H 2 /g CdS/h), which was the highest record for CdS QDs. This finding demonstrated the possibility to well control the crystalline structure of biosynthesized QDs by simple bio‐metabolism regulation and provided a bio‐metabolism‐driven green route for crystalline engineering.